Integration of the Western Balkan Countries and Turkey in the Framework Programmes: Some Empirical Evidence - Švarc, Jadranka; Perković, Juraj; Lažnjak, Jasminka (2013)
The paper discusses results of empirical research focused on the barriers to cooperation of Western Balkan countries and Turkey (WBC&T) in EU Framework Programmes (EU FP). 1 It reveals that WBC&T and member states of EU share a very similar pattern of barriers dominated by ‘Project managing weaknesses’ and ‘Bureaucratic barriers of the European Commission’. However, same barriers present much greater difficulties to researchers from WBC&T due to low intensity in international research cooperation, weak mobility and specific socio-political factors like political instability and scientific inferiority. The weak participation of WBC&T in FP is an obstacle not only to integration of WBC&T into the ERA but also slows down overall cohesion process that is nowadays dependent on human capital and innovation capacities supported by research. Therefore, the balance between social cohesion policy and scientific-merit research policy should be put in place.
Projekt MZOS
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG